A comparative study on productivity and temperament of N'dama cattle under two management systems and N'dama and West African Shorthorn under the same management system - Appiah, P. (1988)
A comparative study of N'Dama and West African Shorthorn (WASH). Records of N'Dama and WASH herds under different management systems were analysed to determine and compare productivity and temperament of the breeds between 1973 and 1987. There were no significant differences between the two breeds in temperament, carcass characteristics and productivity indices.